Interpretação Ambiental e Ecoturismo Urbano: Uma Proposta para o Município de Ponta Grossa- PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Environmental Interpretation seeks to connect scientific knowledge about natural and cultural heritage with observers, promoting the revelation of meanings and relationships through personal experiences. This process aims to raise social awareness of conservation. In the context of ecotourism activities, including urban environments, Digital Information and Communication Technologies (DICTs), such as QR codes, stand out as tools capable of enriching the interpretive experience. Thus, this dissertation investigates the relationship between trees in the urban space and ecotourism practices, using Environmental Interpretation as the central approach. The general objective is to analyze the interpretive potential of selected trees through digital technologies, with the application of QR codes and digital maps. The methodology includes identifying and spatializing the tree species, describing their main attributes, justifying the choice of specimens and locations, and developing a digital map integrated with QR codes, designed to meet the demands of the research. The results indicate a gap in the interpretation of urban natural heritage in Ponta Grossa, Paraná. On the other hand, the adoption of digital tools shows a growing interest among society, public authorities and the scientific community, reinforcing the potential of these technologies for scientific dissemination and promoting sustainability.
Keywords: Interpretação Ambiental; Ecoturismo; Árvores; Novas Tecnologias; Environmental Interpretation; Ecotourism; Trees; New Technologies; CNPQ::CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS